2020
DOI: 10.1017/s1754470x20000197
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy for co-morbid anxiety and depression in heart failure: a case report

Abstract: Abstract Heart failure increases the likelihood of an individual experiencing co-morbid anxiety and depression, which can affect their physical as well as mental health. There is a need to develop non-pharmacological interventions for the psychological consequences of heart failure. Evidence shows that cognitive behavioural therapy (CBT) can be helpful, but there is less clarity about CBT’s effectiveness for people with heart failure who have complex multi-morbid difficultie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The study characteristics and results are summarized in Table 1. [17][18][19][20][21][22][23][24][25][26] Gary et al 17 conducted an RCT in stable New York Heart Association (NYHA) class II to III HF patients with depression. The effectiveness of a combined 12-week home-based exercise/CBT program was compared with CBT alone, exercise alone, and usual care.…”
Section: Resultsmentioning
confidence: 99%
“…The study characteristics and results are summarized in Table 1. [17][18][19][20][21][22][23][24][25][26] Gary et al 17 conducted an RCT in stable New York Heart Association (NYHA) class II to III HF patients with depression. The effectiveness of a combined 12-week home-based exercise/CBT program was compared with CBT alone, exercise alone, and usual care.…”
Section: Resultsmentioning
confidence: 99%
“…Depression and/or anxiety symptoms reduced from moderate to mild or asymptomatic on psychometric scales for all cases except for 'Ray' who scored above clinical cut-off for the duration of therapy (Birdsey, 2020). There were self-rated reductions in helplessness, memoryrelated worry and embarrassment (Richardson and Marshall, 2012), increased confidence and/ or activity (Harris and Hiskey, 2015;Richardson and Marshall, 2012), increased social contact (Walshe and Allen, 2020) and reduction in emergency bed days (Slaughter and Allen, 2020). It is interesting to speculate why Ray, the youngest of the case studies, receiving over three times as many sessions as any of the other case studies, showed the least symptom reduction.…”
Section: Discussionmentioning
confidence: 97%
“…Worry management, sleep hygiene, motivational self-statements and relapse prevention were also used in more than one case. Two of the case studies labelled their approach 'transdiagnostic CBT' (Slaughter and Allen, 2020;Walshe and Allen, 2020) and two combined CBT with compassion-focused therapy (Birdsey, 2020;Harris and Hiskey, 2015). All included between-session tasks.…”
Section: Intervention (I) Duration and Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…This was found to be effective in reducing scores on scales of depression and anxiety and proved cost effective. Two case studies from the subsequently created PINC Service, have further indicated this efficacy (Slaughter & Allen, 2020;Walshe & Allen, 2020). As such it was felt that AB's presentation of comorbid anxiety and depression with an LTC that left her housebound, would be best served by PINC, as the preference was to deliver face-to-face therapy in the client's home.…”
Section: Case Conceptualizationmentioning
confidence: 95%